(untitled) (Hackensack, N.J., 2005)
This comprehensive volume of articles from the seventh school on non-accelerator astroparticle physics presents a timely coverage of this interesting and rapidly expanding subject. The contributions enlarge and complement the earlier volumes prepared for the fourth, fifth and sixth schools. An informative, pedagogical approach has been maintained so that the book can serve as the basis for a modern course on the subject. The first section introduces the fundamentals of particle physics with a review of the standard model and beyond. The comprehensive section on neutrino physics and astrophysics covers neutrino masses and oscillations, short and long baseline neutrino experiments, atmospheric and solar neutrinos, and neutrino telescopes. The section on dark matter includes a theoretical presentation and a review of existing and potential dark matter searches. Searches for axions, magnetic monopoles, and nuclearites are also discussed.
Keywords: Nuclear astrophysics,Particles (Nuclear physics); Hạt nhân vật lý thiên văn,Phân tử (vât lý hạt nhân